Applications of fiber optic sensors in engineering mechanics : a collection of state-of-the-art papers in the applications of fiber optic technologies to civil structures - Ansari, Farhad (American Society of Civil Engineers, 1993)
Eight papers report to civil engineers the latest research in applying fiber optic technology to such infrastructure applications as measuring strain, temperature, pressure, and magnetic fields; smart structures; fracture mechanics; and embedment in concrete. Annotation c. by Book News, Inc., Portland, Or.